How to save neonatal calves from Scours - Gupta, V K; Yadav, Sanjay K; Ramkumar, P K; Khurana, K L (Indian Farming, 2015)
In neonatal calf mortality, calf scour is an important cause, among the causes of mortality in calves. Therefore, managers or health experts of dairy farm can reduce the calf deaths in their farm and earn maximum profit by applying/ following the precautions, suggestions, described in the article.